Effectiveness of Nurse-Led Interventional for Preventing Complications of Postoperative Open Heart Surgery - Azeez, Nadia Bahir; Atiyah, Hussein Hadi (Iraqi National Journal of Nursing Specialties, 2024)
Objective (s): The aim of this study is to determine the effectiveness of an interventional program on the knowledge of nursing staff toward the prevention of post-operative open heart surgery complications. Methods: A quasi-experimental design was conducted for the timeframe 26th of December, 2022 to the 2ed of April, 2023. A non-probability purposive sample was used to select 60 nurses working in the intensive care unit, the data was gathered through a questionnaire filled out by the nurses. The descriptive and inferential statistic was used to analyze the data by SPSS. Results: The findings in the study group reveal that nursing staff are showing poor level of knowledge during the pre-test time among all items of the scale; during the post-test time, the findings indicate that nursing staff are demonstrating good knowledge across all scale items. While the nursing staff in the control group show fair level of knowledge during the pre-test time among all items except item 10 that show good. During the post-test time, they show poor level of knowledge among all items except item 10 that show good Conclusions: The interventional program served as an effective instructional tool for boosting nurses’ knowledage of how to prevent complications following open heart surgery. Recommendations: Nurses should be trained in the prevention of post-operative open heart surgery complications and more studies should be done regarding the prevention of post-operative open heart surgery complications.